ANALISIS KESIAPAN RUMAH SAKIT DALAM PENERAPAN SISTEM INFORMASI MANAJEMEN DI RSU DR. F. L. TOBING, SIBOLGA - , Rugun Simanjuntak; , Dr. Techn. Khabib Mustofa, S.Kom, M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Hospital performance improvement can be achieved by the availability of computer technology-based management support named hospital information system (HIS), which requires internal and external environment support in its application. The hospital of Dr. F.L. Tobing Sibolga has not yet utilized computer-based information system. Objective: This study aims at exploring readiness of Dr. F. L. Tobing hospital in utilization of information system, particularly in terms of human resources, availability of IT infrastructure, planning and policy, budget availability, organizational structure, local government support, and information management. Methods: The study was conducted at Dr. F.L. Tobing hospital at District of Sibolga, North Sumatera. This study used qualitative descriptive case study design. Survey was conducted to 272 respondents to assess the readiness of hospital human resources by distributing questionnaires to gain user perception about their capabilities in operating computer. Observation was conducted by identifying the availability of hospital readiness supporting documents to adopt IT as well as the availability of IT infrastructure. Interviews were conducted to 16 respondents to gain their perception about the readiness components prepared by organization to HIS adoption such as human resources, strategic planning, budget and finance, IT management and support, IT infrastructure, local government support, and information management. First, literature review was conducted to design the assessment instrument, namely California Community Clinic EHR Assessment and Readiness (CCCEAR), which has been modified, with three levels of readiness, namely 1) not yet ready (score 0-33), 2) moderately ready (34-66), 3) highly ready (67-100). Next, findings from the questionnaires, observations, and interviews were outlined and then assessed using the instrument. Lastly information gathered from the assessment was scored and analyzed qualitatively. Result: Descriptive analysis of skill in operating computer showed that human resources readiness was in ready category ( 75%) which score was 77,32%. The qualitative analysis showed that the hospital was in the first level (not yet ready), with a score of 31 by researcher as first assessor and 26 by expert as second assessor. It indicates that the hospital of Dr. F.L. Tobing is not currently prepared to move forward with HIS adoption, but has considered developing a more comprehensive plan to determine how to build the capacity to ensure successful adoption and use. Conclusion: The hospital of Dr. F. L. Tobing Sibolga is not currently ready yet in early adoption of hospital information system.